Perizinan Hotel di Dinas Perizinan Kota Yogyakarta Dalam Perspektif Good Governance - Nurainun Mangunsong (UIN Sunan Kalijaga Yogyakarta, 2016)
This paper will examine the pattern of licensing policy and transparency. By using empiricaljuridical methods for the study of the results showed that administrative regulations and policiesbased on the Mayor and the Department of Licensing, the licensing policy patterns are in one townspatial layout system. That is, the hotel licensing should consider public spaces such as parking lots,green open spaces, access roads and transfortasi or mobility; social, economic, and health, especiallyhotel and water waste; and the construction of the addition of the road itself. Congestion be gaps inthe issue of granting the permit. On the other hand, the information service system through theInstitute of Integrated Services One-Stop Unit (UPTSA) with the licensing process remains in theagency/SKPD either conventionally or on-line (http://www.jogjakota.go.id., And http://perizinan.jogjakota.go.id), already provide services quickly and professionally. Ineffectiveness occurin the implementation of the technical authority on education and transparency of licensingverification and oversight of the hotel.